USE OF MORINGA SEED (Moringa oleifera Lam.) AS A BIOCOAGULANT TO IMPROVE SURFACE WATER QUALITY - Bravo Vidaurre, F. (2023)
Using Moringa oleifera (Moringa oleifera Lam.) seed as a biocoagulant to enhance surface water's physical and chemical quality was the goal of this study. The methodology applied for the generation of experimental data was through the use of the Jar Test equipment, in a dose of 40 mg/L to 140 mg/L, then a fast mixing of 100 rpm for 1 minute and a slow mixing of 40 rpm for 10 minutes was performed, and sedimentation was left for 5 to 30 minutes, with 5 minutes intervals between each dose. The results show that an optimal biocoagulant dose of 100 mg/L at 20 minutes produced a turbidity reduction effectiveness of 97.06%. Hardness fell by 12% of its starting value, conductivity and total dissolved solids increased dramatically, and there was a 92.3% reduction in perceived colour, which showed that the use of Moringa seeds as a coagulant had a favourable effect on reducing the concentration of turbidity and colour. Because of this, Moringa (Moringa oleifera Lam.) can be used as a natural source to purify drinking water. The Tukey HSD test applied to the turbidity removal percentages, indicates that the means are not significantly different. However, the experimental evaluation indicates that after 20 minutes, the best results are obtained.